Comparative Studies on Quality and Starch Digestibility of Hydrocolloid Fortified Sweet Potato Pasta Dried at Low and High Temperatures - Padmaja, G (JOURNAL OF ROOT CROPS, 2015)
Although sweet potato [Ipomoea batatas (L) Lam] has various nutritional advantages like low glycaemic index, high antioxidant potential and dietary fiber content, it is not extensively cultivated and utilized in most parts of the world. The present study aims at adding value to this root crop through the development of functional pasta fortified with gum sources such as guar gum, xanthan gum, locust bean gum and partially hydrolyzed guar gum. The pasta products were dried at low (55 °C) and high (70 ºC) temperatures and it was found that high temperature drying reduced the cooking loss and raised the swelling index for all the fortified pastas. In vitro starch digestibility of cooked pasta indicated only a progressive glucose release from 20 to 120 min, with decreased digestibility for the 70 °C dried pastas than those dried at 55 °C. Rapidly digested and slowly digested starch fractions were lower for the pasta dried at 70 ºC than 55 °C, while the undigested or resistant starch was higher for samples dried at 70 ºC. Increasing the level of fortification of gums from 1% to 3% reduced the starch digestibility further.Highest firmness on cooking was obtained for the xanthan fortified pasta (70 ºC dried), while it had the lowest adhesiveness at 3% fortification. It was concluded from the study that fortification of sweet potato pasta with 1% gum and drying at 70 °C could produce pasta with low starch digestibility, good swelling index and textual characteristics, suggesting its use as food for the diabetic and obese people.